2008
DOI: 10.1109/tbcas.2008.2003430
|View full text |Cite
|
Sign up to set email alerts
|

On the Thermal Elevation of a 60-Electrode Epiretinal Prosthesis for the Blind

Abstract: In this paper, the thermal elevation in the human body due to the operation of a dual-unit epiretinal prosthesis to restore partial vision to the blind affected by irreversible retinal degeneration is presented. An accurate computational model of a 60-electrode device dissipating 97 mW power, currently under clinical trials is developed and positioned in a 0.25 mm resolution, heterogeneous model of the human head to resemble actual conditions of operation of the prosthesis. A novel simple finite difference sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The basic geometry for the rabbit eye is taken from a chapter by Gwon,16 while the retinal and choroidal layers are taken from the in vivo rabbit model by Sramek et al 9 The thermal properties of the tissue layers were derived based on the reported water content of each layer, [17][18][19] assuming that the heat capacity and thermal conductivity would be the scaled average of the properties of water and hydrated proteins 20,21 which make up the remainder of the material. The density of tissue was assumed to be that of pure water or fat 22 at 37°C. The optical absorption coefficients for the retinal and choroidal layers were taken from the 1064 nm data in Hammer et al 23 Since protein has negligible absorption in the near-IR, the remaining ocular layers were assumed to have absorption coefficients proportional to the water content.…”
Section: Thermal Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic geometry for the rabbit eye is taken from a chapter by Gwon,16 while the retinal and choroidal layers are taken from the in vivo rabbit model by Sramek et al 9 The thermal properties of the tissue layers were derived based on the reported water content of each layer, [17][18][19] assuming that the heat capacity and thermal conductivity would be the scaled average of the properties of water and hydrated proteins 20,21 which make up the remainder of the material. The density of tissue was assumed to be that of pure water or fat 22 at 37°C. The optical absorption coefficients for the retinal and choroidal layers were taken from the 1064 nm data in Hammer et al 23 Since protein has negligible absorption in the near-IR, the remaining ocular layers were assumed to have absorption coefficients proportional to the water content.…”
Section: Thermal Modelmentioning
confidence: 99%
“…In this model, we derived them for each tissue layer from reported water content, which made them somewhat different from those in previously reported models. 22,33,34 A careful measurement of these properties is likely to improve temperature calculations slightly, but the greatest source of uncertainty is the absorption coefficients. These are not as easily defined and vary by position in the eye, from subject to subject and from species to species.…”
Section: Damage Threshold Temperaturesmentioning
confidence: 99%
“…(50) In terms of neural stimulators, stimulation safety is related to two main factors: power dissipation at tissue and by implanted electronics, and charge balancing (zero net remaining charge after biphasic current stimulation). A rise in temperature of 1-2 ℃ above the normal body temperature could lead to tissue damage; (51) therefore, the total power dissipation of the implanted stimulator should be less than tens of mW to prevent an excessive rise in temperature. Maintaining charge balance during electrical stimulation is also important.…”
Section: Current Stimulatorsmentioning
confidence: 99%
“…• C [5] with high stimulation Paul Jung-Ho Lee and Amine Bermak are with the Smart Sensory Integrated Systems (S2IS) Lab, the Department of Electrical and Computer Engineering, Hong Kong University of Science and Technology, Clear Water Bay, Hong Kong, China (e-mail: jhleeaa@ust.hk, eebermak@ust.hk).…”
Section: Introductionmentioning
confidence: 99%